2010
DOI: 10.1515/sg-2010-0005
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Diploid Eggs With Colchicine During Embryo Sac Development in Populus

Abstract: Diploid (2n) eggs were induced by treating developing embryo sacs of Populus with colchicine solution, in order to produce triploid plants. The optimal pollinated time of female catkins was confirmed as timing point for each treatment. When female catkins of P. pseudo-simonii x P. nigra ‘Zheyin3#’ had become 5.62 ± 0.13 cm long 84 h after they emerged from their bract scales and all stigmas were exposed, pistils all over the entire catkin had optimal stigma receptivity. Observation of paraffin sections showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 21 publications
2
51
0
Order By: Relevance
“…Reports on triploid production via induction of 2n eggs are rare in Populus, because it is difficult to determine the exact stage of megasporogenesis, which processes inside of ovules of a whole flower (WANG et al, 2010). However, based on the analysis of the temporal relationship between megasporogenesis and microspore development which allowed the optimal time for colchicine treatment to be determined, LI et al (2008) obtained up to 16.7 % triploid plants by inducing unreduced megaspores at the prophase of the first meiotic division in P. alba x P. glandulosa.…”
Section: Use Of Diploid Gametesmentioning
confidence: 99%
“…Reports on triploid production via induction of 2n eggs are rare in Populus, because it is difficult to determine the exact stage of megasporogenesis, which processes inside of ovules of a whole flower (WANG et al, 2010). However, based on the analysis of the temporal relationship between megasporogenesis and microspore development which allowed the optimal time for colchicine treatment to be determined, LI et al (2008) obtained up to 16.7 % triploid plants by inducing unreduced megaspores at the prophase of the first meiotic division in P. alba x P. glandulosa.…”
Section: Use Of Diploid Gametesmentioning
confidence: 99%
“…Both colchicine and high temperature are usually used to induce polyploids in plants ( Randolph 1932;Särkilahti and Valanne 1990;Zhang et al 2002;Dhooghe et al 2010). In the genus Populus, colchicine has been used to successfully induce 2n pollen, 2n eggs and somatic chromosome doubling (Mattila 1961;Kang et al 2000;Ewald et al 2009;Wang et al 2010), producing both triploids and tetraploids. Recently, Wang et al (2012a, b) reported 2n female gamete induction with high-temperature treatment during megasporogenesis and embryo sac development, resulting in the production of a number of triploid plants.…”
Section: Discussionmentioning
confidence: 99%
“…P. × canadensis 'Zhonglin-46', P. × canadensis 'Sacrau 79', P. × liaohenica, P. × langfangensis-3 and triploid clones of P. tomentosa, have been widely deployed in artificial plantations because of their good growth properties and pulpwood characteristics. In order to obtain triploid plants of Populus, unilateral sexual polyploidization via induced 2n male or female gametes has been widely studied (Mashkina et al 1989a;Kang et al 2000;Li et al 2008;Wang et al 2010;Wang et al 2012a, b). More than 60% triploid production efficiency can be achieved via hybridization with induced 2n female gametes (Wang et al 2010;Wang et al 2012b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations